The kinetics of albumin metabolism in experimental protein calorie malnutrition - Kirsch, Ralph E (Department of Medicine, 2020)
Protein Calorie Malnutrition (PCM) is a term which embraces the broad spectrum of diseases occurring where diets are poor in protein. In most cases the diseases are due to an inadequate intake of utilizable protein. A small percentage of cases are due to excessive protein loss, (e.g. burns, nephrosis·, protein loosing enteropathy) or to defects in protein· absorption (gastro-enteritis, steatorrhoea) or synthesis (liver disease). Where the caloric intake is relatively normal the disease produced, kwashiorkor, is characterised by retardation of growth and development, muscular wasting, oedema and psychic changes, usually peevishness or apathy. In addition, some cases have skin lesions and the colour and texture of the hair is often abnormal. Diarrhoea is almost constant in the recent history and is usually present on admission to hospital. The disease is most common in children who have recently been weaned.